2021
DOI: 10.55047/cashflow.v1i1.20
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Capital Adequacy, Liquidity and Firm Size on Earnings Management With Corporate Governance as Moderating Variables in Conventional Banking Listed on Idx 2015 – 2019

Abstract: With corporate governance as a moderating variable, this study intends to examine the impact of capital adequacy, liquidity, and firm size on earnings management. This study's population consists of 45 conventional banks that were listed on the Indonesia Stock Exchange between 2015 - 2019. Purposive sampling was used to choose the sample, which resulted in a total sample of 33 firms. Multiple regression analysis using Eviews 9 software is the analytical technique used to test the hypothesis. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
9

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 12 publications
1
9
0
9
Order By: Relevance
“…Similar studies conducted by several researchers are (Anggriawan, 2014;Faradina, 2016;R. J. Harahap &;Tobing, 2020;Indrayani et al, 2019;Irawan et al, 2018;Kusumawaty &;Betri, 2019;Laitupa &;Hehanussa, 2020;Masri et al, 2022;Moalina &;Wulandari, 2018;Novita, 2015;Rafnes &;Primasari, 2020;Salsabil, 2019;Sania et al, 2019;Tandijono et al, 2018;Yuanita &;Amanah, 2018;Citra et al 2021) concluded that work experience has a positive effect on fraud detection. Based on the description above, the hypothesis in this study is formulated as follows: H 2 : Work experience has a positive effect on fraud detection.…”
Section: The Effect Of Work Experience On Fraud Detectionsupporting
confidence: 54%
“…Similar studies conducted by several researchers are (Anggriawan, 2014;Faradina, 2016;R. J. Harahap &;Tobing, 2020;Indrayani et al, 2019;Irawan et al, 2018;Kusumawaty &;Betri, 2019;Laitupa &;Hehanussa, 2020;Masri et al, 2022;Moalina &;Wulandari, 2018;Novita, 2015;Rafnes &;Primasari, 2020;Salsabil, 2019;Sania et al, 2019;Tandijono et al, 2018;Yuanita &;Amanah, 2018;Citra et al 2021) concluded that work experience has a positive effect on fraud detection. Based on the description above, the hypothesis in this study is formulated as follows: H 2 : Work experience has a positive effect on fraud detection.…”
Section: The Effect Of Work Experience On Fraud Detectionsupporting
confidence: 54%
“…Meningkatkan kinerja perusahaan adalah kepentingan terbaik manajemen karena akan memungkinkan mereka untuk mendapatkan imbalan yang dibutuhkan. Dalam skenario ini, manajemen memiliki peluang untuk menurunkan beban pajak yang ditanggung perusahaannya dengan memanfaatkan penyusutan aset tetap perusahaan (Citra et al, 2021;Sianturi et al, 2021).…”
Section: Pengaruh Capital Intensity Terhadap Penghindaran Pajakunclassified
“…Hasil penelitian yang dilakukan oleh Darmawan & Sukartha (2014) menunjukkan ROA berpengaruh terhadap tax avoidance, sedangkan penelitian yang dilakukan oleh Putri & Putra (2017a) yang menujukkan ROA tidak berpengaruh terhadap praktik penghindaran pajak." Kasmir (2016) mengemukakan bahwa Leverage merupakan rasio yang dapat digunakan dalam mengukur sejauh mana aktiva perusahaan dapat dibiayai oleh utang, yang dalam arti lain rasio ini untuk mengukur kemampuan perusahaan dalam membayar seluruh kewajiban jangka pendek dan jangka panjangnya (total utang/total asset) (Citra et al, 2021). "Dalam penelitian ini Leverage diproksikan dengan Debt to Equity Ratio (DER), Semakin tinggi nilai rasio Leverage semakin tinggi pula jumlah pendanaan dari utang pihak ketiga yang digunakan oleh perusahaan dan semakin tinggi pula biaya bunga yang timbul dari utang tersebut.…”
Section: Pendahuluanunclassified